Analisis Pengalaman Pengguna Aplikasi Sistem Informasi Puskesmas Paperless menggunakan Metode Usability Testing dan User Experience Questionnaire (UEQ) (Studi Kasus : Puskesmas Tarik Kabupaten Sidoarjo) - Wibiansya Analis Febrianto; Widhy Hayuhardhika Nugraha Putra; Andi Reza Perdanakusuma (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Tarik Health Center is one of the health centers located in the Sidoarjo Regency. In conducting medical record services using website-based application information technology, namely Paperless Health Center Information System (SIMPLE). In using the SIMPLE application, users who are internal employees of the Puskesmas From these considerations, the research conducted on analyzing user experience in using SIMPLE applications. The process of analyzing the SIMPLE application user experience is done using the usability testing method and user experience questionnaire (UEQ). The stages carried out in this study are literature study, data collection, data processing, discussion, discussion and gathering conclusions and suggestions. Tests of usability testing are carried out on 3 SIMPLE application users who produce values, namely for the aspect of effectiveness, the results are 100%, which means users can complete the task given, the efficiency aspects get 100%, which means the time needed is good and aspects of satisfaction use the usability scale (SUS) system questionnaire obtained a result of 68.12 which means that the satisfaction level of SIMPLE application users depends on the marginal high. Furthermore, for testing user experience, UEQ questionnaires were distributed to 25 respondents and produced scores on perspicuity aspects, dependability aspects, attractiveness aspects, efficiency aspects, stimulation aspects and novelty aspects having an average value of 1.137 which means SIMPLE application users tend to positive.